Does personality functioning influence perception of social distance amongst Czech students studying in an international university, a state university and the general population? - Su Luo; Marek Preiss; Edel Sanders (Acta Psychologica)
This study investigates the differences of personality functioning and attitudes toward minorities amongst Czech university students and the general population. Utilizing the newly developed scale measuring the concept of personality functioning (Level of Personality Functioning Scale - LPFS), the Modern Racism Scale (MRS), the Blatant and Subtle Prejudice Scale (BSPS) and the Bogardus Social Distance Scale, we compared 75 Czech students from an international university and a state university with 55 general population participants. The results show that students exhibited higher levels of impairment in personality functioning and more negative attitudes toward minorities compared to the general population. Unexpectedly, students from the international university had more pronounced levels of social distance and prejudice compared to students from the state university while having similar levels of personality functioning impairment. Our study confirms the positive relationships found between personality functioning and attitudes toward minorities in previous studies. Future research should examine socio-economic influences and the interplay between personality functioning and defense mechanisms in shaping social perception.